Green synthesis, characterization and antibacterial, antifungal, larvicidal and anti-termite activities of copper nanoparticles derived from Grewia asiatica L. - Tahir, Arifa (2023)
From the literature, it is very clear that almost every section of the Angiosperms can be used to biosynthesize nanoparticles (Valli and Suganya 2016). In the present experiments, brown-colored and fine nanoparticles were synthesized by centrifugation followed by re-dispersing the pallets in the double-distilled water.